Recent Advances on Coagulation-Based Treatment of Wastewater: Transition from Chemical to Natural Coagulant - Bahrodin, Muhammad Burhanuddin; Zaidi, Nur Syamimi; Hussein, Norelyza; Sillanpää, Mika; Prasetyo, Dedy Dwi; Syafiuddin, Achmad (Current pollution reports, 2021)
Purpose of Review The use of conventional chemical coagulant in treatment of wastewater is gaining great attention. Drawbacks related to the prolonged effects on human health and environment due to the generation of by-product non-biodegradable sludge are becoming the latest topics. Transition from chemical to natural coagulant can be a good strategy to reduce the aforementioned drawbacks. Therefore, this review aims to provide critical discussions on the use of natural coagulant along with the comparative evaluation over the chemical coagulant. Recent Findings Treatment performances by chemical and natural coagulant have been reviewed on various types of wastewater with different success rates. Based on this review, a transition from the use of chemical to natural coagulant is highly suggested as the performance of the natural coagulant is comparable to that of the chemical coagulant and in some cases even better. The comparative advantages and disadvantages also convinced that the natural coagulant stands a great chance to be used as an alternative over the chemical coagulant. Summary Though the current utilization of natural coagulant is encouraging, three main aspects were overlooked by researchers: active coagulant agent, extraction, and optimization due to different wastewater characteristics. Furthermore, delving into these aspects could clarify the uncertainties on the natural coagulant. Hence, it makes this transition a prospect of green technology with sustainable application towards wastewater treatment.